The Impact of HRM Practices in Relation to Commitment and Retention of Talented Employees - Aisha Banu, Palle Buela White, Poonam, Jugunu R Nair, Ajit Kumar, Veenashri M (Journal of Informatics Education and Research, 2024)
Effective HRM practices are pivotal in creating a work environment that motivates employees, fosters a sense of belonging, and aligns individual goals with organizational objectives. In essence, HRM practices are foundational to nurturing a committed and stable workforce. They play a critical role in shaping the employee experience, driving organizational success, and ensuring long-term sustainability. By prioritizing employee commitment and retention through thoughtful and strategic HRM practices, organizations can secure a loyal and skilled workforce, ready to meet future challenges and opportunities. The research design is developed to provide a suitable structure for carrying out a study. Choosing a research strategy is a vital part of study design, since it determines the approach for gathering relevant information. The main data is collected using a questionnaire (Google form) that is filled out by a group of participants. The study included a sample size of 200 employees drawn from population. Convenient sampling is used for gathering data from individuals who are willing to take part in a research study. The results indicate that the development of a dedicated workforce and the reduction of attrition rates are significantly influenced by the implementation of comprehensive training programs, equitable performance evaluation systems, and competitive compensation packages. The implications of these findings underscore the significance of strategic HRM practices in the development of a productive and loyal workforce, which, in turn, contributes to organisational success.